Current State and Development Trends of Education Policy Research in China in the Last Decade (2004–2013): A Statistical Analysis of Papers from Eight Core Chinese Journals. Issue 3 (4th May 2017) - Ling, Guo
Abstract: The author conducted sampling and statistical analysis of papers on education policy research collected by the China National Knowledge Infrastructure in the period from the years 2004–2013. Under the current state of education policy research in China, the number of papers correlates positively with the year; the papers are concentrated in education journals; the researchers are primarily associated with institutions of higher education; and the studies cover a broad range of topics, while emphasizing the practice of education policy. The development trends of education policy research in China include a general rising trend for research on education policy; in the future, researchers from institutions of higher education will continue to be a dominant force in education policy research, and the authors' regional distribution will continue to be imbalanced; education policy research will focus more on educational equity and improved quality, and studies of foreign education policies will continue to be a topic of interest.